Educational Recommendations for Medical Students Regarding Assessment and Management of Patients of Undifferentiated Criticality - Andrew S. Hyde; Carlos E. Brown (Trauma Care)
Classical medical education teaches history and physical skills using scenarios wherein the criticality of a patient is predefined. This educational approach creates a gap in medical knowledge for students, who do not regularly define or establish patient criticality, and this gap is realized when it comes to the triage and management of critical patients. The purpose of this paper is to define an approach to patient assessment and management that is accessible to medical students regardless of criticality. This approach is algorithmic and defined by the use of three steps: (1) a primary survey, during which a general impression of the patient is formed, ABCDEs are assessed, and a criticality assessment is made; (2) a secondary survey, during which vitals, history, and exam data are all collected to form a working diagnosis; and (3) plan and treatment, during which supportive diagnostics, such as labs, imaging, and testing, are performed in the service of patient stabilization and intervention, consults/referrals are ordered/placed, and a final disposition is established. This model is intended to complement existing medical education and further expand it to encompass both critical and noncritical patients.